2010
DOI: 10.3109/01612840903254859
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Economic Skill Building Intervention to Promote Women's Safety and Child Development in Karachi, Pakistan

Abstract: Violence against women is a global epidemic phenomenon that can result in major mental health problems. Not only are women affected but also the health and well-being of their children are in jeopardy. To prevent violence and promote women's safety, several strategies have been tested in various cultural contexts. This article describes the process of developing and validating an economic skill building intervention for women of an urban slum area of Karachi, Pakistan. The purpose of the intervention is to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The traditional model has been research ‘on’ communities and subjects rather than ‘with’ them, and the clarification of intentions and establishment of trust is crucial to overcome possible negative preconceptions [19,59,60]. Often, an academic research team conceives the studies and the community partners feel that they must constantly advocate for the abidance of community-based principles (which may be overlooked in the interests of time or funding guidelines).…”
Section: Cbpr Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional model has been research ‘on’ communities and subjects rather than ‘with’ them, and the clarification of intentions and establishment of trust is crucial to overcome possible negative preconceptions [19,59,60]. Often, an academic research team conceives the studies and the community partners feel that they must constantly advocate for the abidance of community-based principles (which may be overlooked in the interests of time or funding guidelines).…”
Section: Cbpr Challengesmentioning
confidence: 99%
“…While CBPR has the ability to empower communities to make themselves healthier, it is not always feasible owing to the large amount of time required to develop and cultivate trusting partnerships [19,59,60]. This time constraint may limit progress for CBPR to demonstrate improved healthcare outcomes [68–71].…”
Section: Cbpr Challengesmentioning
confidence: 99%
“…These micro‐enterprises, frequently generated by micro‐credit loan programmes, require training for skills ranging from information technology (Prasad & Sreedevi ) to conflict resolution (Hirani et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Micro‐credit loans are another example of formal economic support facilitating economic solvency (Hirani et al . ). While a woman must be free of economic assistance from outside sources to meet the current definition of economic solvency, use of resources is necessary to achieve economic solvency.…”
Section: Resultsmentioning
confidence: 97%
“…In various contexts, this has been seen as improving family relationships (Pick, Contreras, & Aguilar, 2006) and marital synchronization (Rogers & Deboer, 2001). The study conducted in Pakistan concluded positive outcomes of the economic skills building modules training (Hirani et al, 2010) where women reported increased self-efficacy, self-awareness, and better marital and family relationships .…”
Section: Economic Skill Buildingmentioning
confidence: 94%